2019
DOI: 10.1371/journal.pone.0225441
|View full text |Cite
|
Sign up to set email alerts
|

Healing The Past By Nurturing The Future: A qualitative systematic review and meta-synthesis of pregnancy, birth and early postpartum experiences and views of parents with a history of childhood maltreatment

Abstract: BackgroundChild maltreatment can have serious effects on development and physical, social and emotional wellbeing. Any long-lasting relational effects can impede the capacity to nurture children, potentially leading to ‘intergenerational trauma’. Conversely, the transition to parenthood during pregnancy, birth and the early postpartum period offers a unique life-course opportunity for healing. This systematic review aims to understand the pregnancy, birth and early postpartum experiences of parents who reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 69 publications
1
21
0
Order By: Relevance
“…While mothers’ reported that CMEs do not represent a current active threat, they nonetheless may inform empathic responses to infants in a way that seeks to repair their own prior childhood experiences as has been suggested in qualitative analyses (i.e. ‘I want my infant’s life to be different than mine’) ( Chamberlain et al. , 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…While mothers’ reported that CMEs do not represent a current active threat, they nonetheless may inform empathic responses to infants in a way that seeks to repair their own prior childhood experiences as has been suggested in qualitative analyses (i.e. ‘I want my infant’s life to be different than mine’) ( Chamberlain et al. , 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it seems to be quite feasible to ask about ACEs and mental health and expect co-operation from the majority. The time interval around childbirth might thus constitute a window of opportunity [ 32 ]. Questions that would normally be regarded as an intrusion of privacy and cause unease in health care staff might thus be accepted willingly and this might help to understand better what kind of assistance might be needed in order to improve the future of the couple and the child [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was most true for couples where both members were exposed to multiple ACEs, as shown in the present study. Global action to prevent and diminish these consequences must be the obligation for every society and is in accordance with the sustainable goals of the UN [ 32 , 35 ]. These preventive and therapeutic efforts demand development of a new concept of primary care/general practice/health care as a whole, social welfare services as well as staff in schools with broadened competences in meeting, understanding and helping people afflicted by ACEs and other demanding life conditions [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…For some, pregnancy and birth empowers women to take control of their own bodies and challenges the memory of the abuse by focusing on the body as a site of growth, rather than of abuse. Further, it may supplant negative memories with ones of pride in their creation (Chamberlain et al, 2019;LoGiudice & Beck, 2016). Research suggests pre-emptive work can be undertaken to improve labour (Gerber, 2019;Sperlich et al, 2017), such as: creating birth plans (Rhodes & Hutchinson, 1994), prioritising trusting relationships with HCPs (Florian, 2018;Montgomery, 2013), and respecting privacy (Parratt, 1994).…”
Section: Introductionmentioning
confidence: 99%